Impacts of emotional intelligence and spiritual intelligence on leadership effectiveness mediated by personal values: a conceptual framework - Osman-Gani, Aahad M.; Anwar, Md. Aftab; Abdul Hamid, Zabeda (World Academy of Islamic Management (WAIM), 2017)
Research on emotional intelligence (EI) and spiritual intelligence (SI) in the workplace is still in the early stage of HRD and Management fields. Particularly, these constructs have not been studied enough from the perspectives of personal values and leadership effectiveness. Successful leaders manage and guide employees by using their own preferred approaches, value subordinates’ feelings about their work, and intervene appropriately to enhance their self-esteem and motivation. But, these issues have not been properly addressed in Management and HRD literature. This paper proposes a conceptual framework by showing the potential relationships existing among emotional intelligence, spiritual intelligence and leadership effectiveness, mediated by personal values. After conducting a review and analysis of relevant literature, the authors developed five propositions which could be tested through future empirical research. Future research may be conducted to identify the relationship existing among emotional intelligence and spiritual intelligence and personal values in different national cultural contexts. Organizational top management should consider making appropriate decisions for nurturing and developing emotional and spiritual intelligences among leaders and identify their value system that would make significant contributions to their performance effectiveness. Implications for future research and for professional practice are also discussed at the end.